Advances on aerodynamic actuation induced by surface dielectric barrier discharges - Portugal, Sherlie; Choudhury, Bhaswati; Cardenas, Dorindo (Frontiers in Physics, 2022)
Surface Dielectric Barrier Discharge (SDBD) is a well-known technology for active aerodynamic flow control with low power consumption. It is a type of plasma actuation for flow control with no moving parts and very fast response times. Research on SDBD flow control over the years has shown great potential for flow separation, boundary layer transition, drag reductions and suppression of local heating. A major area of research on SDBD flow control lies in increasing the effectiveness of SDBD actuators with new electrode configurations, surface materials, and plasma array designs. This review aims to provide a comprehensive report of research performed on SDBD flow control over the last two decades with a focus on SDBD reactor designs. Aspects of SDBD flow control including discharge morphology and actuation mechanism through momentum and energy transfer have been discussed in depth. Additionally, the future of research in SDBD actuated flow control has been explored. This review can serve as the baseline to develop new SDBD reactor designs for specific applications with improved effectiveness and advanced systems.